ALTERATION RELATED TO HYDROTHERMAL ACTIVITY OF THE NEVADO DEL RUIZ VOLCANO (NRV), COLOMBIA (2012)
The hydrothermal activity in the NRV generates alteration characterized by mineral associations depending ona number of physic-chemical factors of the hydrothermal system. Petrography of unaltered rocks was used toestablish the mineral assemblage prior to rock-fluid interaction. XRD was used in altered rocks, where it was not possible to recognize the alteration products. The observed mineral assemblages indicate advanced and intermediate argillic alterations, this and the observation of very low modal proportion of sulphates, sulphidesand native sulphur in some areas could point to a low sulphidation zone. However, the proximity to the volcano and the presence of acid thermal waters and steam pose an apparent contradiction with an expected high sulphidation zone which is explained by climatic conditions, where excess water has dissolved and leached sulfides, sulphur and sulphates close to the volcano. Fault zones serve as conducts for fluid transport and haveacid-sulphate mineral associations produced by atmospheric oxidation at the water table in a steam-heatedenvironment of H2S released by deeper, boiling fluids or by the disproportionation of magmatic SO2 to H2Sand H2SO4 during condensation of magmatic vapor plume at intermedia depths in magmatic hydrothermal environment in andesitic volcanic terrain characteristic of high sulphidation zones. Keywords: Hydrothermalalteration, Nevado del Ruiz, Volcano.